Radiographic and spectral images of rice seeds and the photosynthetic efficiency of seedlings - Artur Sousa Silva; Silvio Moure Cicero; Francisco Guilhien Gomes Junior (Scientia Agricola, 2024)
ABSTRACT The development and the use of new technologies in agriculture contribute to significant advances in research with practical applications in several fields, such as image analytical techniques, which are simple, fast, and objective analyses. This work aimed to evaluate rice seeds’ quality using X-ray, multispectral, and chlorophyll fluorescence image analytical techniques and relate this information with the photosynthetic efficiency of seedlings. Initially, the seeds were identified and enumerated, then X-ray images were obtained, and the void space (area between the endosperm + embryo and the glumes) was calculated. Next, the same seeds were used in the X-rays, multispectral, and chlorophyll fluorescence images. Afterward, the seeds were placed to germinate in polyethylene cups with a capacity of 250 mL, and evaluations of the photochemical yield of photosynthesis photosystem II (FSII) and of the seedling fluorescence chlorophyll were carried out seven, nine, and 11 days after the emergence of the seedlings. The reflectance of seeds in the spectral bands between 365 nm and 780 nm showed a positive correlation with the chlorophyll fluorescence. Furthermore, the higher photosynthetic efficiency of rice seedlings at 11 days after emergence is directly related to the reflectance of the seeds at spectral bands between 365 nm and 780 nm.